2018
DOI: 10.3389/fchem.2018.00104
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Defluoridation Capacity From Aqueous Media via Hydroxyapatite Decorated With Carbon Nanotube

Abstract: In this work, the potential of a novel hydroxyapatite decorated with carbon nanotube composite (CNT-HAP) for fluoride removal was investigated. The synthesized CNT-HAP composite was systematically characterized by X-ray diffraction(XRD), Fourier Transform infrared spectroscopy(FTIR), scanning electron microscope (SEM) and Brunauer–Emmett–Teller(BET). Batch adsorption experiments were conducted to investigate the defluorination capacity of CNT-HAP. The CNT-HAP composite has a maximum adsorption capacity of 11.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 47 publications
2
13
1
Order By: Relevance
“…Therefore, this parameter determines the rate of mass transfer from the solution to the surface of the adsorbent, and the data were used to study the kinetic study of batch adsorption. This trend was also reported by other studies on defluoridation processes [11,18]. This is due to the faster saturation of the active sites with time.…”
Section: Defluoridation Efficacy Of Ha On Prepared Fluoride Solutionsupporting
confidence: 87%
See 2 more Smart Citations
“…Therefore, this parameter determines the rate of mass transfer from the solution to the surface of the adsorbent, and the data were used to study the kinetic study of batch adsorption. This trend was also reported by other studies on defluoridation processes [11,18]. This is due to the faster saturation of the active sites with time.…”
Section: Defluoridation Efficacy Of Ha On Prepared Fluoride Solutionsupporting
confidence: 87%
“…The experimental equilibrium adsorption capacity and the calculated capacity are close to the R 2 value of 0.999 [34]. This indicated that it is unity and the adequate linear fitting of the plots confirmed that the adsorption of fluoride ions using the synthesized hydroxyapatite followed pseudo-second-order kinetics [15,18].…”
Section: Adsorption Kinetic Modelssupporting
confidence: 65%
See 1 more Smart Citation
“…Tang et al investigated the defluoridation of water by using novel hydroxyapatite decorated with carbon nanotube composite (CNT-HAP) [56]. Maximum adsorption capacity using CNT-HAP composite for removal of fluoride was found to be 11.05 mg/g at pH 6.…”
Section: Carbon-based Pristine and Functionalized Nanomaterialsmentioning
confidence: 99%
“…With the rapid development of the chemical industry, F − has come to exist not only in the aqueous environment but also in organic media such as fluoride anion-containing pesticides and waste organic liquor (Clark, 1980). Recognition and detection of fluoride in organic solvent with a simple sensor and minimal instrumental assistance are imperative for practical applications (Yang et al, 2013;Kaur and Choi, 2015;Curnow et al, 2018;Tang et al, 2018;Murfin et al, 2020). Among various F − sensors, fluorescence sensors have been widely investigated due to their multiple advantages .…”
Section: Introductionmentioning
confidence: 99%